Ayn Rand and the Posthuman The Mind-Made Future - Murnane, Ben (Springer International Publishing, 2018)
Ayn Rand and the Posthuman is a study of the American novelist's relationship with twenty-first-century ideas about technology. Rand wrote science fiction that has inspired Silicon Valley entrepreneurs, politicians, and economists. Ben Murnane demonstrates Rand's connection to, and impact on, those with a "posthuman" vision, in which human and machine merge. The text examines the philosophical intersections between Rand's philosophy of Objectivism and posthumanism, and Rand's influence on transhumanism, a major branch of posthumanist thought. The book further investigates Rand's presence and portrayal in various examples of posthumanist science fiction, including Gene Roddenberry's Andromeda, popular videogame BioShock, and Zoltan Istvan's novel The Transhumanist Wager. Considering Rand's influence from a cultural, political, technological, and economic perspective, this study throws light on an under-documented but highly significant aspect of Rand's legacy.